DEVELOPMENT OF ACTIVE FAULT MAPPING METHOD USING GEOELECTRIC AND GEOGRAPHICAL INFORMATION SYSTEM (GEOMATE Journal, 2024)
On February 25th, 2022, an earthquake with a magnitude of 6.2 in Nagari Kajai, Talamau District, West Pasaman Regency, resulted in considerable structural damage because it originated from a shallow earthquake with a hypocenter depth of 12.6 km and is a manifestation of the strike-slip faulting system linked to the Sumatra Fault System (SFS), which is adjacent to the Angkola segment, Barumun Segment, Sumpur Segment, and Sianok Segment is a newly-found active fault in this area. All of Nagari Kajai (Kajai Village) Sub-district is covered in volcanic deposits, whether they are new (quaternary deposits) or a combination of old (tertiary deposits) and young (quaternary deposits) as a product from the Talamau Mountain and the Maninjau Mountain. These geological activities will provide a good impression of the topography and geomorphology of a newly found active fault, The Kajai Fault. The geomorphological analysis is used to get new characteristic features for this new fault line continuation using Landsat 8 imagery and supported by aerial photography using Unmanned Aerial Vehicles (UAV). A 2D subsurface image was obtained from the Wenner-Schlumberger geoelectric survey configuration to get an excellent subsurface interpretation of lithology in this area. From this interpretation, the Kajai Fault is present in a valley filled with volcanic products and a narrow diversion of the Batang Talu River. The geoelectrical survey images show a double juxtaposition from two interpreted faults, namely F1 and F2, which run through The Kajai village and are suspected to be one of the shallow earthquake sources.